2012
DOI: 10.1016/j.cllc.2011.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Promoter Methylation of CDH13 and MGMT Genes is Associated With Clinicopathologic Characteristics of Primary Non–Small-Cell Lung Carcinoma

Abstract: Introduction Systemic methylation changes may be a diagnostic marker for tumor development or prognosis. Here, we investigate the relationship between gene methylation in lung tumors relative to normal lung tissue, and whether DNA methylation changes can be detected in paired blood samples. Material and methods Sixty five patients were enrolled in a surgical case series of non-small cell lung cancer (NSCLC) at a single institution. Using bisulfite pyrosequencing, CpG methylation was quantified at five genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 14 publications
0
28
0
5
Order By: Relevance
“…Methylation/demethylation profiles of many genes have been linked with normal development and differentiation (4 -6) as well as with cancer initiation and progression. Systemic methylation changes in certain tumor-related genes were also suggested to be diagnostic markers for tumor development or prognosis (7,8). Moreover, the self-renewal of normal hematopoietic (9, 10), neural (11), and embryonic stem cells, as well as cancer stem cells (12), is also suggested to be controlled by methylation of specific genes.…”
mentioning
confidence: 99%
“…Methylation/demethylation profiles of many genes have been linked with normal development and differentiation (4 -6) as well as with cancer initiation and progression. Systemic methylation changes in certain tumor-related genes were also suggested to be diagnostic markers for tumor development or prognosis (7,8). Moreover, the self-renewal of normal hematopoietic (9, 10), neural (11), and embryonic stem cells, as well as cancer stem cells (12), is also suggested to be controlled by methylation of specific genes.…”
mentioning
confidence: 99%
“…(Table 2). These same tumor-suppressor genes are frequently found to be hypermethylated and inactivated during carcinogenesis in general, and lung cancer in particular (Kontic et al, 2012; Nikolaidis et al, 2012). Further, the level of hypermethylation of these genes significantly correlated with the cumulative doses of radon among the miners (cumulative exposure dose range 12±6 – 294±132; z=3.859, P =0.0001).…”
Section: Ionizing Radiation and Gene-specific Dna Methylationmentioning
confidence: 99%
“…RASSF1A-M sense primer:5'GTGTTAACGCG TTGCGTATC3', RASSF1A-M antisense primer: 5'AACCCCGCGA ACTAAAAACGA3', The amplification product was 119bp; RASSF1A-U sense primer: 5'TTTGGTTGGAGT G T G T TA AT G T G 3 ' , R A S S F 1 A -U a n t i s e n s e primer:5'CAAACCCCAC AAACTAAAAACAA3', The amplification product was 125bp.CDH13-M sense:5'TCGCGGGGTT CGTTTTTCGC3', CDH13-M antisense: 5'GACGTTTTC ATTCATACACGCG3', The amplification product was 243bp; CDH13-U sense:5'TTGTGGGG TTGTTTTTTGT3', CDH13-U antisense: 5'AACTTTTCAT TCATACACACA3', The amplification product was 243bp (Qiang et al, 2009;Vo et al, 2013;Milica et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Because of the methylation of promoter region is a reversible process, detection of gene methylation levels may provide guidance for the individualized chemotherapy (Blattler et al, 2013). It has been suggested that methylation of RASSF1A and CDH13 genes promoter region is closely related to the occurrence of NSCLC.As tumor suppressor gene, RASSF1A and CDH13 genes methylation occur frequently in NSCLC (Jung et al, 2012;Milica et al, 2012).…”
Section: Introductionmentioning
confidence: 99%